ANALISIS IMPLEMENTASI REGULASI ZAKAT: (Kajian di UPZ Desa Wonoketingal Karanganyar Demak) - Murtadho Ridwan (Program Studi Hukum Keluarga Islam, 2016)
This article analyzes the implementation of Zakat‟s regulation in UPZ Wonoketingal Villlage. Data were gathered through documentation and interviews. Result shows that collecting process of zakah condected by UPZ Wonoketingal is in accordance with regulations. UPZ has collected zakat of wealth every harvest time and personal zakat every year. However, its distributions seems to violate the Article of 46 (3) of PP No 14 Year 2014. Despite its limitations, UPZ Wonoketingal presents weekly report on their program after Friday prayer. The report is also sent to BAZCAM.